ULTRA-VIOLET SPECTROPHOTOMETRIC METHOD FOR VALIDATION OF CARBOCISTEINE FROM BULK DRUG AND PHARMACEUTICAL FORMULATION - RELE RAJAN V.; PATIL SACHIN S. (International Journal of Pharma and Bio Sciences, 2013)
A simple, rapid, sensitive and precise UV spectrophotometric method have been developed for the estimation of carbocisteine from bulk drug and pharmaceutical formulation. In this method carbocisteine showed maximum absorbance at about 200.4 nm in 0.1N HCl. Beer’s law was followed in the concentration range of 10 to 140 μg/ ml. Regression equation was found to be y = 0.0067 x – 0.0015 and coefficient of correlation was 0.9999 . The proposed method is accurate, sensitive, reproducible and useful for the estimation of carbocisteine from bulk drug and pharmaceutical formulation.